ANALISIS PENDAPATAN PETANI TAMBAK UDANG VANAME DI DESA RANDUTATAH KECAMATAN PAITON KABUPATEN PROBOLINGGO - Sunaika, Sunaika; Fahrudin, Fahrudin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Shrimp farmers in Randutatah village chose vaname shrimp because these shrimp have a fairly high selling value, the management system is short and does not require a large amount of capital. This research aims to determine the process of cultivating vaname shrimp in Randutatah Village. And regarding the income of shrimp farmers in cultivating vaname shrimp in Randutatah Village. The type of research used is a qualitative method, the data in this research was obtained from primary data and secondary data, the data collection techniques used were observation, interviews and documentation. The research results show that the production process of vaname shrimp cultivation in Randutatah Village consists of: 1.) production planning that takes into account production factors such as land, labor and capital. 2.) the production process which includes the procurement and selection of seeds. 3.) The final production process is the process of harvesting the vaname shrimp culture. The income of shrimp farmers in Randutatah village fluctuates due to price, area and weather factors. The highest income from Mr. H. Abdullah is IDR 232,000,000 with 1,629 meters. Meanwhile, Mr. Hafif's lowest income was IDR 162,422,000 with 2,800 meters because he was a new shrimp farmer and had only reached the fifth cycle. And lack of experience and knowledge.